2007
DOI: 10.1084/jem.20071416
|View full text |Cite
|
Sign up to set email alerts
|

JAM-A regulates permeability and inflammation in the intestine in vivo

Abstract: Recent evidence has linked intestinal permeability to mucosal inflammation, but molecular studies are lacking. Candidate regulatory molecules localized within the tight junction (TJ) include Junctional Adhesion Molecule (JAM-A), which has been implicated in the regulation of barrier function and leukocyte migration. Thus, we analyzed the intestinal mucosa of JAM-A–deficient (JAM-A−/−) mice for evidence of enhanced permeability and inflammation. Colonic mucosa from JAM-A−/− mice had normal epithelial architectu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
258
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 430 publications
(274 citation statements)
references
References 32 publications
13
258
0
3
Order By: Relevance
“…acted as barrier-forming TJ proteins in fish [22,23,73], whereas Claudin-12 and Claudin-15 acted as pore-forming TJ proteins in mice [74]. Moreover, studies showed that decreased Claudin-b, -3, Occludin and ZO-1 mRNA levels in fish [23], and up-regulated Claudin-12 and Claudin-15 gene expression in mice [75,76] impaired TJ barrier function. Present study showed that compared with appropriate riboflavin supplementation, riboflavin deficiency up-regulated Claudin-12 and down-regulated Claudin-c, -3, Occludin and ZO-1 mRNA expression in the gills of young grass carp ( Fig.…”
Section: 23mentioning
confidence: 99%
“…acted as barrier-forming TJ proteins in fish [22,23,73], whereas Claudin-12 and Claudin-15 acted as pore-forming TJ proteins in mice [74]. Moreover, studies showed that decreased Claudin-b, -3, Occludin and ZO-1 mRNA levels in fish [23], and up-regulated Claudin-12 and Claudin-15 gene expression in mice [75,76] impaired TJ barrier function. Present study showed that compared with appropriate riboflavin supplementation, riboflavin deficiency up-regulated Claudin-12 and down-regulated Claudin-c, -3, Occludin and ZO-1 mRNA expression in the gills of young grass carp ( Fig.…”
Section: 23mentioning
confidence: 99%
“…JAM‐A regulates apical actomyosin contraction, and deficiencies lead to enhanced MLC2 phosphorylation 36. However, unlike in mice with JAM‐A deficiency 35, CerS2 null mice did not show increased epithelial proliferation and formation of large lymphoid aggregates. A possible explanation for this is that JAM‐A was only partially decreased in the colons of CerS2 null mice.…”
Section: Discussionmentioning
confidence: 90%
“…Mucin dysfunction 33, 34 and JAM‐A deficiency 35, 36 have been shown to cause increased intestinal permeability, especially under basal conditions, with an enhanced susceptibility to experimental colitis. Thus, we evaluated mucin production in CerS2 null mice.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations